Effects of exercise intervention on tobacco dependence: a meta-analysis - Xu, Jinzhi; Zhang, Shiyue; Chen, Zichao; Wu, Zhusheng (Frontiers in Public Health, 2025)
IntroductionSmoking poses a significant threat to global human health, making smoking cessation a controllable means of preventing mortality. Exercise, as a means of promoting a healthy lifestyle, offers substantial benefits to individuals attempting to quit smoking. However, due to variations in experimental populations and conditions, the specific effects and benefits of exercise on smoking cessation remain unclear. In this meta-analysis, we comprehensively evaluated the withdrawal effects of different intensities of exercise on tobacco-dependent individuals.MethodsStatistical analysis and graphing were performed using Stata 14 and Review Manager 5.4 software. A total of 47 literatures, encompassing 57 randomized controlled trials and involving 4,267 tobacco-dependent individuals, were included.ResultsThe meta-analysis results showed that long-term exercise had no significant difference or impact on the degree of tobacco dependence between the exercise and control groups. However, acute exercise was associated with increased tobacco craving (desire and intensity) and more pronounced withdrawal symptoms.DiscussionAcute aerobic exercise can significantly reduce craving and withdrawal symptoms among individuals attempting to quit smoking, demonstrating a certain role in smoking cessation. Acute aerobic exercise emerges as the most effective form of physical exercise for intervening in tobacco dependence.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, CRD42024550014.